DISABILITY AND MENTAL HEALTH AS A PROFESSIONAL LIVE STREAMER - Johnson, Mark Richard (AoIR Selected Papers of Internet Research, 2020)
In this paper I explore economic and inclusion opportunities for people with disabilities and mental health issues afforded by ‘live streaming’ ‒ the live broadcast of one’s activities over the internet to a globally dispersed audience. In both 2016 and 2017, the leading live streaming platform Twitch.tv broadcast over 500,000 years of video, which were produced by over two million regular broadcasters (‘streamers’), and consumed by an audience of several hundred million viewers. Streamers can profit, up to and including a full-time living ‘wage’ for those at the highest levels. Numerous successful streamers with chronic health issues have discussed the personal and professional benefits streaming brings them. Utilising data from a research project with 100 interviews, alongside approximately 500 hours of ethnographic observation, this paper examines the experiences of live streaming for broadcasters with disabilities, mental health issues, or physical health issues. Firstly, I explore the positive elements of streaming for these broadcasters, focusing on the many conditions represented in this demographic, and the benefits streaming gives for inclusion and community. Secondly, I consider the negative experiences of these streamers, focused on entanglements of health and technology that make their streaming lives potentially more challenging than their colleagues. Thirdly, I focus on the economic opportunities, and the potential for entrepreneurial activity, the platform affords. I conclude the analysis by exploring how these aspects make live streaming a potentially exemplary emancipatory and entrepreneurial space for these individuals, but not one without challenges.